Educational Activity: A Preliminary Review and Some International Experiences - Salem Ali Al Qahtani; Asyraf Isyraqi Jamil; Fakhrul Adabi Abdul Kadir (Ta'allum: Jurnal Pendidikan Islam, 2017)
This paper reviews the history of the educational activity which was entered through John Dewey’s Experimental School, founded in 1896, the first school to use the activity curriculum. It sheds the light on the stages that activity has gone through till today. The Islamic view and a number of quotes from a number of Islamic thinkers and educators also were reviewed. The importance of the activity, its basics, functions, types and classifications were also discussed. The research concluded with a number of international experiences which gave great importance to the activity in their curricula and educational plans. The most important recommendations are: 1) Offering advanced training programs for teachers on educational activity; 2) Adding educational activity as an independent material in educational colleges; 3) Expanding the scope of study for international experiences in educational activity; and 4) Making use of technology and employing it in the educational activity.